Whether integrating refining and petrochemical business can provide opportunities for development of petrochemical industry in Serbia - Popovic, Zoran; Soucek, Ivan; Ostrovskii, Nickolay; Ocic, Ozren (Hemijska industrija, 2016)
Since the beginning of 90s of last century both the petroleum industry and petrochemical industry have operated in difficult circumstances. In particularly, margins of petroleum and petrochemical industry were exacerbated during global economic crisis in 2008-2009 years. At that time, as one option that could be the solution, the global analysts had started to more intense investigate the benefits of Refining-Petrochemical Integration. Shortly afterwards, more and more petroleum refineries and petrochemical manufacturers began to see the future in this kind of operational, managerial, marketing and commercial connection. This paper evaluates, in particular, the achieved level of integration of refinery and petrochemical businesses in Central and South-Eastern Europe. And specifically, the paper identifies current capabilities and future chances of linking this kind of integration between Serbian refining and petrochemical players. The viability of integration between possible actors and benefits of every single refining-petrochemical interface in Serbia depend on many factors, and therefore each integrated system is unique and requires prior serious Cost Benefit Analysis. nema